2009
DOI: 10.1017/s0958344009990085
|View full text |Cite
|
Sign up to set email alerts
|

New competencies in a new era? Examining the impact of a teacher training project

Abstract: This article describes follow-up research aimed at exploring the long-term impact on participants of a teacher training course that integrated a variety of projects focusing on ICT use in language teaching. Internet in education is often promoted for its features that allow for new opportunities for constructivist approaches in the classroom. Nevertheless, this will not simply happen on its own. Teacher education must help shift students teachers’ pedagogical premise toward approaches that promote autonomous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 19 publications
1
55
0
3
Order By: Relevance
“…Previous research exploring language teachers' computer literacy skills has been conducted in Asia (Albilirini, 2006;Aydin, 2013;Chen, 2012;Li & Walsh, 2011;Park & Son, 2009;Shin & Son, 2007;Son, Robb, & Charismiadji, 2011;Sumi, 2010;Yunus, 2007), Europe (Dooly, 2009;Fuchs, 2006), North America (Fuchs & Akbar, 2013;Kessler & Plakans, 2008;Lam, 2000;Meskill, Anthony, Hilliker-Vanstrander, & You, 2006;Wiebe & Kabata, 2010), and South America (Barsotti & Martins, 2010). It has been demonstrated that increased access to technology facilities does not guarantee that language teachers would always integrate CALL into their instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research exploring language teachers' computer literacy skills has been conducted in Asia (Albilirini, 2006;Aydin, 2013;Chen, 2012;Li & Walsh, 2011;Park & Son, 2009;Shin & Son, 2007;Son, Robb, & Charismiadji, 2011;Sumi, 2010;Yunus, 2007), Europe (Dooly, 2009;Fuchs, 2006), North America (Fuchs & Akbar, 2013;Kessler & Plakans, 2008;Lam, 2000;Meskill, Anthony, Hilliker-Vanstrander, & You, 2006;Wiebe & Kabata, 2010), and South America (Barsotti & Martins, 2010). It has been demonstrated that increased access to technology facilities does not guarantee that language teachers would always integrate CALL into their instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than a decade later, surveys conducted in Spain with primary teachers (Dooly, 2009) and France with secondary school language teachers (Guichon, in press) indicate that, although the use of technologies has seen a rise for personal and professional purposes, few changes can be detected in actual pedagogical practices (see also Fuchs, 2008). Dooly (2009) suggests that the gap might still be too wide between how technologies are presented during training programmes and what teachers are really able to do once they start their professional life. This imbalance raises an issue also underscored by Parks et al (2003): institutional and contextual factors have hardly been taken into account in most studies dealing with language teachers' use of ICT.…”
Section: Assessing the Use Of Technologies In Teachers' Practicesmentioning
confidence: 99%
“…Teachers' attitudes have been found to be one of the decisive factors when it comes to using ICTs in language teaching 1 (Kessler, 2007;Dooly, 2009;Guichon, in press) as 1 The first large study in this regard covering different school subjects was the Apple Classrooms of Tomorrow (ACOT) Project which ran for 10 years. The findings were published by Haymore Sandholtz et al (1997).…”
Section: Pre-and In-service Teachers' Attitudes Towards Technologiesmentioning
confidence: 99%
“…Kitade, 2012; see also Beatty, 2013). Teachers then see themselves faced with various challenges that call for organizational, pedagogical, technological, intercultural, and socio-affective competencies in order for the telecollaboration to be conducted successfully (Dooly, 2009;Lomicka & Lord, 2011;O'Dowd, 2013O'Dowd, , 2015. In a similar vein, other teacher educators have highlighted the need to foster STs' intercultural communicative competence (Hauck, 2010;M€ uller-Hartmann, 2005), and autonomy and multiliteracy skills (e.g.…”
mentioning
confidence: 99%